Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1073/pnas.96.23.13536
|View full text |Cite
|
Sign up to set email alerts
|

Long-term expression of protein kinase C in adult mouse hearts improves postischemic recovery

Abstract: Activation of protein kinase C (PKC) protects the heart from ischemic injury; however, its mechanism of action is unknown, in part because no model for chronic activation of PKC has been available. To test whether chronic, mild elevation of PKC activity in adult mouse hearts results in myocardial protection during ischemia or reperfusion, hearts isolated from transgenic mice expressing a low level of activated PKC␤ throughout adulthood (␤-Tx) were compared with control hearts before ischemia, during 12 or 28 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…However, similar to wortmannin, chelerythrine treatment resulted in a significant reduction of postischemic recovery of left ventricular function and an increase in myocardial infarct size in female but not in male hearts and eliminated the gender differences in the postischemic recovery and myocardial infarct size. In agreement with the present finding, previous studies showed that chelerythrine had no effect on postischemic function and infarct size in male hearts (Tian et al, 1999;Ding et al, 2004). The effect of chelerythrine on female hearts has not been previously examined.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…However, similar to wortmannin, chelerythrine treatment resulted in a significant reduction of postischemic recovery of left ventricular function and an increase in myocardial infarct size in female but not in male hearts and eliminated the gender differences in the postischemic recovery and myocardial infarct size. In agreement with the present finding, previous studies showed that chelerythrine had no effect on postischemic function and infarct size in male hearts (Tian et al, 1999;Ding et al, 2004). The effect of chelerythrine on female hearts has not been previously examined.…”
supporting
confidence: 82%
“…Control hearts received the vehicle only (0.04% DMSO). The concentrations of wortmannin and chelerythrine were chosen on the basis of reported IC 50 of the inhibitors (5 nM wortmannin; Arcaro and Wymann, 1993;0.66 M chelerythrine;Herbert et al, 1990) and the concentrations used in the previous studies for wortmannin (100 nM) (Fujio et al, 2000;Mockridge et al, 2000;Tong et al, 2000;Bell and Yellon, 2003;Okumura et al, 2004;Tsang et al, 2004) and chelerythrine (2-4 M) (Tian et al, 1999;Mockridge et al, 2000;Stamm et al, 2001;Przyklenk et al, 2003;Ding et al, 2004) in animal models of ischemia and reperfusion injury. In separate experiments, some male hearts were pretreated with 5 M PKC⑀ translocation inhibitor peptide (PKC⑀-TIP; Calbiochem) for 20 min before ischemia and reperfusion with no wash-out period.…”
Section: Methodsmentioning
confidence: 99%
“…22 Body weights and heart weights of the mice used in the experiments were similar among all four groups (Table). Hearts were stabilized for 30 minutes, and baseline function was measured.…”
Section: Ho-1 Improves Recovery Of Cardiac Performance During Reperfumentioning
confidence: 90%
“…Hearts were rapidly excised, arrested in ice-cold buffer, and connected via the aorta to the perfusion cannula as described. 22 Retrograde perfusion was maintained at a constant pressure of 70 mm Hg by gravity. The flow of thebesian veins was drained by a thin polyethylene tube (PE-10) through the apex of the left ventricle (LV).…”
Section: Isolated Perfused Heart Preparationsmentioning
confidence: 99%
“…Second, although numerous hypertrophic signals were shown to activate different PKC isoforms, the bulk of the evidence argues against an involvement of PKC in initiating and/or maintaining hypertrophy (11,28). In fact, upregulation of PKC␤ in the adult heart has been shown to have beneficial effects (75). Importantly, pharmacologic inhibition of PKC did not block AII-induced hypertrophy (74) but did abrogate AII activation of c-fos transcription (62) and ANF biosynthesis (34).…”
Section: Discussionmentioning
confidence: 99%